Evaluation of the Implementation of Productive Zakat in Empowering Mustahik Owned MSMEs - Riska Octavia Habie; Mitra Riani Aisyah; M. Syarif H. Djauhari; Nur Anisa S. Hasan (Sanskara Ekonomi dan Kewirausahaan, 2026)
Productive zakat is one of the Islamic economic empowerment instruments designed to enhance the economic independence of mustahik through the development of sustainable business activities. However, the success of productive zakat programs depends not only on the amount of assistance provided but also on the effectiveness of program implementation. This study aims to evaluate the implementation of a productive zakat program across its major stages, including planning, assistance distribution, mentoring, and monitoring, while examining its contribution to the empowerment of mustahik-owned Micro, Small, and Medium Enterprises (MSMEs). A descriptive qualitative approach was employed, involving productive zakat program administrators and five mustahik beneficiaries as research informants. Informants were selected using purposive sampling based on their direct involvement in the program. Data were collected through in-depth interviews, observations, and documentation and analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The findings indicate that the implementation of productive zakat has followed the prescribed stages of planning, verification, assistance distribution, monitoring, and mentoring. The program has positively contributed to business sustainability and the economic self-reliance of mustahik. Nevertheless, improvements in beneficiaries' income remain limited due to constraints related to business capacity, market access, and the intensity of mentoring. The novelty of this study lies in its comprehensive evaluation of productive zakat implementation from the perspectives of both program administrators and beneficiaries using the Context, Input, Process, and Product (CIPP) evaluation model. The findings highlight the importance of strengthening business mentoring, entrepreneurship training, and capacity-building initiatives to enhance the long-term effectiveness and sustainability of productive zakat programs.